Adoption intensity of a standardized technical system: The higher the better?—Evidence from China - Li, Yu; Hua, Yongjun; Liao, Bing; Yuan, Xiaohao; Zhou, Ziyuan (Frontiers in Environmental Science, 2022)
Under contract farming, companies usually develop compulsory standardized technical systems for farmers to carry out in developing economies. This study investigates the determinants and impacts of adoption intensity of the standardized technical systems on household incomes, using cross-sectional microscopic data from a sample of over 384 households and a multinomial endogenous treatment effects model to correct selection bias and endogeneity caused by observed and unobserved heterogeneities. The results show that some factors affect the adoption intensity significant, such as farmers’ satisfaction with technicians, perception of technology, attitude to-wards risks of adopting technologies, number of technical trainings, proportion of leased land, and distances to townships and technology extension stations. Different from the current experiential judgment, the results also indicate that farmers should select the appropriate adoption intensity instead of highest level according to the characteristics of the plot. Finally, some policy suggests are proposed for farmers to apply the standardized technical system more efficiently.